The use of agglomerated cork as underlay for improvement of impact sound insulation in buildings - António Pedro Oliveira de Carvalho (1999)
Eight different cork agglomerate products were tested to assess their impact sound insulation quality when used as underlay with four different floor coverings (linoleum, ceramic tile and two types of wood parquet). The measurements were made on-site (with flanking transmissions) on a coffered concrete floor and according to the standards EN ISO 140-7 and 717-2. The results show that the use of this underlay improves the weighted normalized impact sound pressure level (L'n,w) for each respective reference floor up to 18 dB (for ceramic tiles), 25 (thin parquet), 25 (linoleum) and 23 dB (thick parquet). Prediction formulas, determined by statistical analysis are presented.